Pengaruh debt to equity ratio dan current ratio terhadap nilai perusahaan dengan return on asset sebagai variabel intervening - Meliani Imanah; Alfinur; Supami Wahyu Setiyowati (Jurnal Riset Mahasiswa Akuntansi, 2020)
This study aims to analyze the effect of debt to equity ratio and current ratio on firm value with return on assets as an intervening variable on food and beverages companies listed on the Indonesia Stock Exchange for the period of 2016-2018. The study uses secondary data from the annual report through access to www.idx.co.id. Data were analyzed using path analysis. The total sample of 13 companies and the method of taking sample members used is purposive sampling. The variables of this study consisted of debt to equity ratio and current ratio as exogenous variables, firm value as endogenous variables, and return on assets as intervening variables. The analysis shows that the debt to equity ratio, current ratio and return on assets have a positive effect on firm value. Debt to equity ratio and current ratio also have a positive effect on return on assets. Based on the results of the path analysis of the implications of this research that return on assets can not affect the relationship between debt to equity ratio and current ratio to the firm value so that it can provide input to researchers. It is better to add research periods and use a sample of several other sectors and can also use variables others that can strengthen the results of previous studies